DUKUNGAN TRANSPORTASI LOGISTIK DAN DAYA SAING INDONESIA DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Sitorus, Budi; Sitorus, Tulus Irfan Harsono (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2017)
The objective of the research is to actualize the reinforcement in the national logistics system, to encourage the creation of reliable and competent logistics human resources and to have the standard of needs set. The fundamental issues in ASEAN regional trade are eliminating existing problems and obstacles, among others (1) the absence of integrated policies and laws and regulations; (2) the limited number and qualification of Logistic and Supply Chain Management (SCM) human resources (3) the high cost in loading and unloading activities at ports; (4) inadequate infrastructure of deep sea transportation in supporting port activities; (5) there are still many less relevant licenses; (6) the excessive licensing time. The research is qualitative descriptive, with concept analysis method. Focusing on a pre-existing concept, to be better understood, described, explained and implemented in the field.